2015
DOI: 10.1038/srep14059
|View full text |Cite
|
Sign up to set email alerts
|

Volatile codes: Correlation of olfactory signals and reception in Drosophila-yeast chemical communication

Abstract: Drosophila have evolved strong mutualistic associations with yeast communities that best support their growth and survival, resulting in the development of novel niches. It has been suggested that flies recognize their cognate yeasts primarily based on the rich repertoire of volatile organic compounds (VOCs) derived from the yeasts. Thus, it remained an exciting avenue to study whether fly spp. detect and discriminate yeast strains based on odor alone, and if so, how such resolution is achieved by the olfactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(150 citation statements)
references
References 59 publications
6
143
1
Order By: Relevance
“…; Scheidler et al . ), we investigated attraction of D. suzukii to H. uvarum and blueberry volatiles in a wind tunnel bioassay. More mated than unmated females responded to yeast and blueberry odours (χ 2 = 7·06, d.f.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Scheidler et al . ), we investigated attraction of D. suzukii to H. uvarum and blueberry volatiles in a wind tunnel bioassay. More mated than unmated females responded to yeast and blueberry odours (χ 2 = 7·06, d.f.…”
Section: Resultsmentioning
confidence: 99%
“…; Scheidler et al . ). Field studies have confirmed D. suzukii attraction to fermentation odours, and yeast volatiles are currently employed in trap lure and attract‐and‐kill formulations (Cha et al .…”
Section: Introductionmentioning
confidence: 97%
“…Yeasts are naturally growing on the surface of rotting fruits and produce volatiles, which attract Drosophilids (Becher et al, 2012; Scheidler et al, 2015). Murphy et al (2016) reported that D. suzukii larval survival rate, number of eggs laid by females and locomotor activity of flies were decreased when the D. suzukii was fed on genetically modified Saccharomyces cerevisiae expressing dsRNA targeting D. suzukii y-tubulin 23C ( yTub23C ).…”
Section: Novel Delivery Methodsmentioning
confidence: 99%
“…Pseudomonas putida has been shown to produce volatiles that attract the olive fly, Bactrocera oleae Gmelin (Liscia et al 2013), and numerous bacteria have been shown to produce volatiles that attract the Oriental fruit fly, Bactrocera dorsalis (Hendel), and the Mexican fruit fly, Anastrepha ludens (Loew) (Jang and Nishijima 1990;Robacker et al 1998). Similarly, a recent study on yeasts isolated from the larval frass and adult midguts of spotted-wing drosophila, Drosophila suzukii Matsumura, and their fruit food source, found a specific association between the flies and some yeasts with a preference for Hanseniaspora uvarum (Scheidler et al 2015). The volatile compounds produced by mutualistic microorganisms living inside host insects that have a symbiotic relationship with plants might trigger their trophic interaction (Frago et al 2012).…”
Section: Introductionmentioning
confidence: 91%